The Influence of Teachers' Professional Competence and Students' Learning Styles on The Learning Achievement of Students - Ani Linsiyah; Siti Yulaeha; A. A. Ketut Budiastra (Universitas Cokroaminoto Palopo, 2023)
The value of teacher professional competence is the basis for student learning success. The purpose of this study was to determine the effect of teacher professional competence and student learning styles on student achievement in grade 4 elementary school. This study uses a quantitative ex post facto approach. The research population used was in the Tembarak sub-district, Temanggung district, with a total of 130 people in 7 elementary schools. The technique used in this study was random sampling so that 98 people were obtained. The results of data analysis were seen through a regression test using SPSS. The results of the study show that the professional competence of teachers has a significant effect on student achievement. Learning styles of students affect the learning achievement of students. And the professional competence of teachers and students' learning styles jointly affect the learning achievements of participants. The implication of this research is that the value of teacher professionalism is not necessarily able to improve student achievement without seeing and analyzing student learning styles in the classroom. So, it is very important for the teacher to know the learning style of each student in the class